Control of crystallographic phases and surface characterization of intermetallic platinum tin nanoparticles. Issue 21 (16th May 2019) - Erdt, Alexandra J.; Gutsche, Christian; Fittschen, Ursula E. A.; Borchert, Holger; Parisi, Jürgen; Kolny-Olesiak, Joanna
Abstract : Colloidal synthesis and characterization of intermetallic tin-rich platinum–tin nanoparticles with detailed surface characterization. Abstract : Tin-rich platinum–tin intermetallic nanoparticles are important catalytic materials. However, their synthesis is still a challenging task. Here, we present an approach to stable, colloidal tin-rich nanoparticles such as PtSn2 and PtSn4 by the reduction of a tin precursor in the presence of preformed platinum seeds. By varying both the size of the platinum seeds and the amount of the tin precursor, we obtain different, colloidally stable, intermetallic platinum–tin phases, such as PtSn, as well as tin-rich PtSn2 and PtSn4 . The resulting, quasi-spherical particles have uniform morphology and narrow size distribution. X-ray diffraction (XRD), total reflection X-ray fluorescence (TXRF) and energy dispersive X-ray (EDX) spectroscopy reveal that all samples are intermetallic instead of random alloys. Furthermore, these measurements provide hints that the surface layer composition differs from that of the core. Therefore, X-ray photoelectron spectroscopy (XPS) measurements were conducted, confirming the presence of a thin tin oxide shell around the particles due to oxidation after exposure to air. In consequence, a crystalline platinum-rich layer forms on top of the core of these nanocrystallites. The detailed structure of this phase was studied by high-resolution transmission electron microscopy (HRTEM).